2012
DOI: 10.1089/gtmb.2011.0212
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association ofCYP1A1Polymorphism with Prostate Cancer Susceptibility of Tunisian Men

Abstract: Cytochrome P450 (CYP)1A1 gene polymorphism has been shown to be associated with several diseases. In this study, we evaluated the association between the polymorphism in the cytochrome P-450 (CYP)1A1 (CYP1A1) gene and genetic susceptibility to prostate cancer (PCa) in Tunisian men. One hundred and thirty eight PCa patients and the same number of controls were enrolled in this study. All DNA samples from peripheral blood leucocytes were genotyped for genetic polymorphism of the CYP1A1 gene using the polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In the present study, no links were detected between PCa and T3801C polymorphism. Our results are consistent with previous reports: Souiden et al [20], Mandić et al [21] found that there is no significant association between T3801C polymorphism of CYP1A1 and PCa in the Tunisian and Caucasian populations, respectively. In addition, the results published by Li et al [22] revealed that no correlation between T3801C polymorphism of CYP1A1and predisposition to PCa.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, no links were detected between PCa and T3801C polymorphism. Our results are consistent with previous reports: Souiden et al [20], Mandić et al [21] found that there is no significant association between T3801C polymorphism of CYP1A1 and PCa in the Tunisian and Caucasian populations, respectively. In addition, the results published by Li et al [22] revealed that no correlation between T3801C polymorphism of CYP1A1and predisposition to PCa.…”
Section: Discussionsupporting
confidence: 94%
“…Seventeen studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] reporting the relationship between CYP1A1 MspI gene polymorphism and prostate cancer susceptibility were included into this meta-analysis (Table 1). Ten studies were performed in Asians, 2 in caucasians, and 3 in Africans.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Similarly, the rhesus system alone may reveal an exclusion, as is the case for example for an O-mother, O + child and O-father [14]. But in some particular cases, such as mother O+, child A1, father O + and if the ABO system is the only exclusion system, paternity is excluded only if it can be shown that one of the parents does not have the Bombay phenotype [15]. On the other hand, the immaturity of antigens in all newborns should be considered; for example, in the following example: mother O, child A2, father A1B, the child's blood type should be checked a few months later before reporting an exclusion, as this may be a delay in the development of the A1 antigen.…”
Section: Discussionmentioning
confidence: 99%